CHARACTER DEVELOPMENT MANAGEMENT FOR ISLAMIC BOARDING SCHOOL STUDENTS IN THE CONTEXT OF DISCIPLINE, LOVE FOR THE MOTHERLAND, AND CARING FOR THE ENVIRONMENT (CASE STUDY AT ISLAMIC BOARDING SCHOOL IN PAGAR KANDANGAN, HULU SUNGAI SELATAN REGENCY) - Abdul Muin; Husnul Madihah; Agustina Rahmi (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Islamic boarding school Dalam Pagar Kandangan, Hulu Sungai Selatan Regency which is in the management of developing the character of Islamic boarding school students in the context of discipline, love of the homeland, and caring for the environment, then in detail consistent and​ sustainable, the world of Islamic boarding schools accompanied by these principles can strengthen the unity and one unity that can become reflection And benchmark so that more prosperous and reach civilization Which brilliant. The aim of this study ; (1) Analyze practice and the management processes carried out in coaching character discipline at the Lodge Boarding school Dalam Pagar Kandangan. (2) Identify various efforts that have been made in coaching character Love homeland. (3) Study the challenges faced in management coaching character care environment, (4) Proposing possible strategies​ applied For overcoming challenges in management coaching characters in the cottage boarding school. The research method used in the research is descriptive qualitative. This research was conducted at Pondok Boarding school Dalam Pagar Kandangan with primary data sources ; Caregivers, Management, Students and secondary data sources ; in the research, namely lodge profile data and lodge history. As for The data collection used by the author is observation, interviews and documentation. Data analysis in qualitative research. Results study This that is ; (1) Management of character development for students with: a) Planning that is affiliated with the understanding of Ahlu Sunnah Wal Jama'ah An Nahdliyah, education is directed at the realm of Tariqah knowledge, religious knowledge, general knowledge and skills. b ) Organizing through optimizing the role of the organizational structure, empowering Madrasah Ibtidayah. c ) Implementation through daily activities of students. d) Control is carried out through evaluation meetings, student regulations or rules of conduct, reorganization of the boarding school management, positive motivation and direction to the students. (2) The efforts made by Islamic boarding schools are collective, creative and innovative, grow love character land water. (3) These challenges include; challenges in implementation, challenges in policy and curriculum, educational personnel challenges and environmental and information technology challenges. (a) environmentally sound policies. (b) implementation of good environmental management, (c) exists development of environmentally friendly facilities and infrastructure in Islamic boarding schools. (d) there are character values that care about the environment. (4) The strategies that can be implemented are: the learning process, the formation of Islamic boarding school culture, co-curricular activities and extra-curricular activities.